IS 600 MYR LONG ENOUGH FOR THE RANDOM PALAEOGEOGRAPHIC TEST OF THE GEOMAGNETIC AXIAL DIPOLE ASSUMPTION? - McFadden P.L. (My University, 2004)
A simple analysis suggests that a time interval of more than about 5000 Myr is needed for the random palaeogeographic test to be effective in assessing the geomagnetic axial dipole assumption. This time is so long as to render the test ineffective. Consequently, intervals of 600 Myr should be recognized as providing only a small sample that is likely to be biased towards low-inclination values.
Keywords: GEOCENTRIC AXIAL DIPOLE HYPOTHESIS; PALAEOMAGNETISM